PENGARUH PENDIDIKAN, KESEHATAN, JAMINAN SOSIAL, DAN PENDAPATAN KELUARGA TERHADAP PARTISIPASI KERJA PENDUDUK LANSIA DI JAWA - Tambunan, Esra Yunike; Arka, Sudarsana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.08.TAHUN.2024, 2024)
The highest population in Indonesia is located on the island of Java. Accompanied by complete health and life support facilities, the life expectancy in the Java region is getting higher, the TFR is low, and the potential for return migration for the elderly is high, resulting in the elderly population in Java growing faster than other regions, which has led to an increase in the elderly dependency ratio. productive population. The problem that occurs is when the elderly do not want to burden the productive age population and still choose to keep working. This study aims to analyze the effect of education, health, social security and family income simultaneously and partially on the work participation of the elderly population in provinces in Java Island. The analysis technique used in this research is panel data regression analysis technique. The results of this study found that education, health, social security and family income simultaneously affect the work participation of the elderly population in provinces on the island of Java. Education and health have a positive and significant effect, social security has a negative and significant effect, while family income has a positive and partially insignificant effect on the work participation of the elderly population in provinces in Java Island.